Practices Of Optimizing the Role of Religious Moderation in Tackling Drugs Abuse - Multazam; Zaim Elmubarok; Darul Qutni; Nadhifah (Genius Journals, 2023)
The objectives of this research are to identify the practice of optimizing the role of religious moderation in preventing millennial generation drug abuse in the city of Semarang and obtaining formulations for achieving the first goal. This research applies a continuous descriptive method which has the characteristics of qualitative research. This method consists of data collection through observation, interviews, documentation, and literature study. The next step is conducting data analysis. The data analysis uses critical techniques. Critical analytical research aims to describe, discuss, and criticize primary ideas confronted with other primary concepts in the effort of comparative studies, relationships, and model development. This topic tends to be complex and depends on many factors, including the potential benefits and considerations related to the role of religious moderation in tackling drug abuse among the millennial generation. Positive Effects of Religion; religious moderation which includes teachings about avoiding risky behavior and practicing moral values can help prevent drug abuse. Spiritual beliefs and a bond with certain religious beliefs can help a person find meaning and purpose in life and reduce the desire to seek temporary gratification through drugs. Community and Support; the religion often involves membership in a community. A healthy religious community provides strong social support, connections with other members who share values and goals, and an understanding that drug abuse is against religious teachings. Education and Awareness; religious moderation includes education and awareness about the dangers of drug abuse among the millennial generation. Religious teachings can be a platform to convey information about the negative effects of drugs on physical and mental health, and their social and legal implications. Ethics and Responsibility; religious moderation teaches ethical, moral values, and personal responsibility which supports millennials make wise decisions and understand the consequences of their actions for themselves and others. Although religious moderation has many benefits, handling drug abuse among millennials still requires a comprehensive and holistic approach. There must be good strategies that involve educational experts, social support, clinical interventions, and collaboration between government, community agencies, and families. All of them play a vital role in addressing drug abuse issues. It is important to remember that each social and cultural context has different views on how to perceive and approach issues like drug abuse. There must also be effective solutions adapted to local needs and challenges
Keywords: Religious moderation; drugs